Mid-range natural orbits around the triple asteroid 2001SN263 - Cavalca, M. P.O.; Gomes, V. M. [UNESP]; Sanchez, D. M. (Springer Nature, 2020)
The goal of the present paper is to search for natural trajectories that can be used to place a spacecraft to observe the triple asteroid 2001SN263. For a first set of observations mid-range distance orbits are ideal. To model this triple asteroid from a mid-range distance, it is considered that it can be modeled as a single ellipsoid body, which gives a simple mathematical model that allows on-board computation of trajectories. The mass is assumed to be equal to the sum of the masses of the three bodies and its dimensions are calculated considering the size of the orbits of Beta and Alpha. The objective is to search for orbits that can be used at the arrival time of the spacecraft in the vicinity of the triple asteroid to observe the bodies to make a better evaluation of their dimensions and dynamics before a good choice for a final orbit can be made. The two-dimensional elliptic restricted three-body problem is used as the mathematical model with the addition of the perturbations coming from the asteroid and the Sun irregular gravity fields (J2). It is also considered the disturbance caused by the solar radiation pressure, a major force near asteroids.